Net buffer load during regional citrate anticoagulated continuous renal replacement therapy. - Innas Forsal; Dominique Pouchoulin; Viktoria Roos; Jorge Echeverri; Marcus Ewert Broman (PLoS ONE)
Background Regionally anticoagulated continuous renal replacement therapy with citrate is the first choice for critically ill patients with acute kidney injury. If citrate that reaches the patient exceeds the metabolic capacity, metabolic alkalosis will follow. Bicarbonate from the treatment fluids will also reach the patient and add to the bicarbonate load. Net buffer load is a parameter calculated by the dialysis machine software from the treatment fluid contents, the fluid flows and the filter properties. Each time the treatment settings are altered the net buffer load will be re-calculated. This parameter is integrated as a static safety parameter in the Prismax version 3 software, and will guide the operator on a possible development of metabolic alkalosis with the current settings. Methods Algorithms for estimating the net buffer load were developed. Hourly clinical data from electronic medical records from 60 patients' continuous renal replacement treatments at the Adult Intensive Care Unit, Skåne University Hospital, Lund, Sweden was used to simulate net buffer load. The relation between net buffer load and acid base status at steady state was evaluated. Net buffer load was also calculated from three previous studies for comparison to our present cohort. Results The mean net buffer load was +0.09 ±0.04 mmol/h/kg in the present cohort, and comparable to historic cohorts from literature. We could not establish a correlation to steady state arterial bicarbonate. The pre blood pump citrate containing replacement fluid flow rate was affecting net buffer load most of all parts of the dialysis circuit, with a r2 Pearson correlation coefficient of 0.65 (p<0.001). Conclusion The net buffer load parameter can alert the operator on the expected impact of the dialysis circuit on patient's acid base status. It was possible to calculate realistic net buffer load values during 60 CRRT treatments.